2022
DOI: 10.3892/etm.2022.11167
|View full text |Cite
|
Sign up to set email alerts
|

Effects of alprostadil combined with hyperbaric oxygen on hearing recovery and hemorheology in patients with sudden sensorineural hearing loss and analysis of related influencing factors

Abstract: The causes of sudden sensorineural hearing loss (SSNHL) are unclear, and the condition cannot be treated with specific regimens. The present study was designed to explore the effects of alprostadil combined with hyperbaric oxygen (HBO) on hearing recovery and hemorheology in patients with SSNHL, and to analyze factors influencing treatment efficacy. in total, 104 patients with SSNHL were enrolled between January 2015 and July 2018 in a randomized controlled trial. Group A (n=52) received alprostadil treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…Ginkgo biloba extract and batroxobin were the most popular drugs applied by Chinese otolaryngologists. Most of the clinical studies supporting the efficacy of these drugs were performed by Chinese researchers, but the quality of studies included in the meta-analysis was low (31)(32)(33). Therefore, higher-quality RCTs assessing the effectiveness of hemorheological drugs are warranted.…”
Section: Combination Therapymentioning
confidence: 99%
“…Ginkgo biloba extract and batroxobin were the most popular drugs applied by Chinese otolaryngologists. Most of the clinical studies supporting the efficacy of these drugs were performed by Chinese researchers, but the quality of studies included in the meta-analysis was low (31)(32)(33). Therefore, higher-quality RCTs assessing the effectiveness of hemorheological drugs are warranted.…”
Section: Combination Therapymentioning
confidence: 99%
“…Hyperbaric oxygen therapy: A controlled trial of 60 ears with hearing impairment and tinnitus that received hyperbaric oxygen therapy and 60 ears that received normoxic therapy found that patients treated with hyperbaric oxygen therapy had significantly better hearing and tinnitus recovery [ 160 ]. Recent studies have found that the combination of alprostadil and hyperbaric oxygen can significantly promote hearing recovery in patients with sudden sensorineural hearing loss by reducing blood viscosity and improving coagulation function [ 161 ]. Hyperbaric oxygen treatment may therefore be a useful complementary therapy.…”
Section: Pathophysiological Mechanisms and Treatment Strategies Of Arhlmentioning
confidence: 99%
“…Previous epidemiological investigations showed that the incidence of SSNHL ranged from 5 to 20 per 100,000 individuals ( Chen et al, 2021 ; Doweck et al, 2022 ). Currently, the pathogenic causes of SSNHL are still debated, and several possible etiologies have been proposed, including viral infection, vascular disorders, trauma and autoimmune diseases ( Shen et al, 2021 ; Wu et al, 2022a ; Feng et al, 2022 ). As a medical emergence, detailed examination to determine possible causes and early treatment onset is extremely important to improve hearing prognosis in SSNHL patients ( Jiang et al, 2021 ; Huo et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%